Duck Meatballs With Various Tuber Flour Quality Based on Organoleptic - Muhammad Yusuf Yasin; Nining Haryuni; Anna Lidiyawati (UNIVERSITAS ISLAM LAMONGAN, 2023)
One of the potential meats for a meatball is duck meat with a fiber arrangement that is almost similar to beef. Flour derived from tubers has the potential to be used as an ingredient for making meatballs because tubers also contain amylopectin, making it chewy and delicious, so that it can have elasticity properties in meatballs. So, it is important to determine the quality of duck meatballs which include color, aroma, taste, texture and level of preference. The research was conducted in the integrated science laboratory of Nahdlatul Ulama Blitar University for 1 month in June. The material used was meatball from duck meat which was bought in the traditional market srengat district blitar, tapioca flour, canna flour, taro flour, porang flour and arrowroot flour and spice which consists of garlic, onion, salt and ice cube. The method used in this study was an experiment laboratory based on Hedonic Test. Data were analyzed with One Way ANOVA and follow by Duncan's Multiple test if significant effect occurs. The results showed that use of different flours on duck meatball gave significant effect (P>0,05) on color, taste, texture, and overall acceptability and did not significantly effect on smell. The characteristic of duck meatball with tapioca flour, canna flour, taro flour and arrowroot flour can be accepted than porang flour.